Perancangan Sistem Informasi Parawisata Kabupaten Pasaman Barat Menggunakan Framework Codeigniter - Maulana Sukma, Ilham; Melladia (Jurnal TEFSIN ( Jurnal Teknik Informatika dan Sistem Informasi), 2023)
The Web of Tourism Information System of Pasaman Barat District is used as a tool in conveying information on tourism and cultural areas in the city of Pasaman to people who want to know or visit tourism areas in the city of Pasaman. The Web of Tourism Information System of Pasaman Barat District is a form of regional tourism promotion in the city of Pasaman, in order to attract tourists to visit the city of Pasaman. This research is expected to be useful as a medium of information and promotion of tourism potential in the city of Pasaman, so that people will be more familiar with regional tourism places in the city of Pasaman. The more tourists who visit, the income of the area and the surrounding community will increase. The research method used is through direct observation, interviews with related parties, and literature study related to the issues raised. The Web of Tourism Information System of Pasaman Barat District was created using the PHP and HTML programming languages ​​with the MYSQL database.